Nanodefects assisted removal of reactive dyes using biomass derived reduced 3D-OGFs. (15th August 2022) - Pandey, Abhishek; Das, Rahul Kumar; Chakraborty, Amit K.; Shukla, Shobha; Saxena, Sumit
Abstract: Water scarcity due to inefficient recycling processes and pollution of water bodies have directly affected the lives and livelihood of around 600 million people globally. Textile industries dump gallons of untreated waste such as dyes, organic reagents, toxic chemicals in surface water. Treating such effluents is a multi-stage process and needs to be addressed urgently. Biomass derived materials have recently gained attention to address these problems. We have investigated remediation of reactive dyes using reduced 3D oxidized graphene frameworks (R-OGFs). Our results suggest that simultaneous reduction and chemical activation results in formation of nanodefects of varying sizes. This induce better aromaticity and thus significantly improve the removal efficiency of reactive dyes. During reduction, the 3D OGFs undergo chemical activation as well. The synthesized R-OGFs removed 99% dye within 150 min with maximum dye adsorption capacity of 48.077 mg/g, following Langmuir isotherm and second order kinetics. The adsorption process and removal efficiency was found to be pH independent, which otherwise forms a major bottleneck in almost all adsorbents and treatment processes. The presence of saline environment (5000 mg/l) not only improved the removal of dye by about 45%, to 99.3% within the first 5 min, but also improved the reusability of R-OGFs. Graphical abstract: Image 1 Highlights: Nanodefects assisted enhanced removal of reactive dyes. pH independent adsorption process. Biomass derived material for water purification. High adsorption capacity for Reactive dyes. Improved performance and recyclability in saline medium.